Understanding the war in Sudan: Scholarly frames, competing narratives, and failed peace - Ylönen, A. (Northeast African Studies, 2024)
Sudan has experienced long periods of war since its independence in 1956. As a common denominator, Sudanese armed conflicts have included a deep-rooted and highly contested identity dimension in the context of nation- and state-building. The protracted conflicts have been primarily interpreted as a struggle of essentialized identities for national identity and the nature of the state and have featured a historically established cultural perception of race and accompanying social hierarchy. Scholars emphasize this attitude and social structure, manifested in identity-based marginalizing political dynamics and repressive, assimilationist, but at the same time exclusionary state policies, mainly along north-south and center-periphery divisions. Scholarly frames of analysis based on this understanding give rise to various narratives of the protracted armed conflicts that are perpetuated by their protagonists and adopted by foreign actors involved in peacemaking. This generates competing views of Sudanese wars and undermines the coherence of efforts to resolve them. The article discusses the role of the major frames of analysis and narratives emerging from them in understanding the complexity of war in Sudan. It argues that the protagonists have perpetuated competing narratives about the essence of the conflict, while external actors have selectively adopted them. This has hindered peacemaking and contributed to the persistent failure of building comprehensive peace.